Regime-Switching Model on Hourly Electricity Spot Price Dynamics - Gyamerah, Samuel Asante; Ngare, Philip (Scientific Research Publishing Inc., 2018)
A robust time-varying regime-switching model for price dynamics of hourly spot price of electricity on the electricity market is developed. We propose a two-state Markov Regime Switching (MRS) model that gives weight to the existence of different variance for each regime. Our model is tractable as it integrates the main features exhibited in the hourly spot price dynamics on the electricity market. The parameters of our hourly spot price of electricity market model are estimated using the Expectation Maximization algorithm. Based on this model, an efficient and tractable pricing technique can be developed to price the dynamics of the hourly spot price of electricity.
Keywords: Regime-Switching Model; Time-Varying Volatility; Hourly Spot Price of Electricity; Expectation-Maximization (EM)-Algorithm